Moving towards community mental healthcare - Ruggeri, M.; Iozzino, L. (Die Psychiatrie, 2016)
Background: After the Psychiatric Reform in 1978 and the closure of large mental hospitals, a nation-wide network of Departments of Mental Health (DMH) has been developed in Italy and now delivers routinely outpatient and inpatient care, and runs semi-residential and residential facilities. Intensive effort has been promoted: inpatient care is provided all over Italy by General Hospital Psychiatric Units (GHPUs) with a maximum of 15 beds, and only a very low proportion of inpatient admissions are compulsory. Community Mental Health Centres are central to mental health services operating between 5 days per week for 12 hours a day in most Regions offering daytime and domiciliary care for those with severe and enduring mental illness; other community mental health services include residential facilities for long-term psychiatric care and day hospital/centres. However, there is still marked quantitative and qualitative variation in the provision of out- and inpatient care throughout the country, and service utilization patterns are uneven. Aim: Further efforts are required to improve quality of care and to develop a more effectively integrated system. Greater attention must be paid to topics such as quality of care and outcomes, and continuous monitoring that orient the overall process of care and particularly psychosocial interventions. Prevention and promotion of mental health, particularly in the early stages of illness, and in adolescence disorders and depression, should be promoted; outcome and quality of care in residential facilities should be targeted to prevent avoidable chronicization.
Keywords: Community care; outcome; residential facilities